Structures of mixed manganese ruthenium oxides (Mn1−xRux)O2 crystallised under acidic hydrothermal conditions. Issue 8 (12th February 2020) - McLeod, Lucy K.; Spikes, Geoffrey H.; Kashtiban, Reza J.; Walker, Marc; Chadwick, Alan V.; Sharman, Jonathan D. B.; Walton, Richard I.
Abstract : Redox hydrothermal chemistry at low pH yields a solid-solution series of β-(Mn1− x Ru x )O2 materials, with structures verified by diffraction and spectroscopy. Abstract : A synthesis method for the preparation of mixed manganese–ruthenium oxides is presented along with a detailed characterisation of the solids produced. The use of 1 M aqueous sulfuric acid mediates the redox reaction between KRuO4, KMnO4 and Mn 2+ to form ternary oxides. At reaction temperature of 100 °C the products are mixtures of α-MnO2 (hollandite-type) and β-MnO2 (rutile-type), with some evidence of Ru incorporation in each from their expanded unit cell volumes. At reaction temperature of 200 °C solid-solutions β-Mn1− x Ru x O2 are formed and materials with x ≤ 0.6 have been studied. The amount of Ru included in the oxide is greater than expected from the ratio of metals used in the synthesis, as determined by elemental analysis, implying that some Mn remains unreacted in solution. Powder X-ray diffraction (XRD) shows that while the unit cell volume expands in a linear manner, following Vegard's law, the tetragonal lattice parameters, and the a / c ratio, do not follow the extrapolated trends: this anisotropic behaviour is consistent with the different local coordination of the metals in the end members. Powder XRD patterns show increased peak broadening with increasing ruthenium content, which is corroborated by electron microscopy that shows nanocrystalline material. X-ray absorption near-edge spectra show that the average oxidation state of Mn in the solid solutions is reduced below +4 while that of Ru is increased above +4, suggesting some redistribution of charge. Analysis of the extended X-ray absorption fine structure provides complementary local structural information, confirming the formation of a solid solution, while X-ray photoelectron spectroscopy shows that the surface oxidation states of both Ru and Mn are on average lower than +4, suggesting a disordered surface layer may be present in the materials.